1997
DOI: 10.1108/00346659710180343
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium: why do we need it and how much is enough?

Abstract: Considers the role of selenium as an essential nutrient. Identifies its key function as being an essential component of a wider range of proteins. Looks at some of the problems related to selenium deficiency such as associations with increased incidence of cancer of heart disease. Reports falling selenium intakes in the UK over the last 15‐20 years and describes a supplementation trial based in Scotland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Under physiological conditions the Se in selenocysteine is almost fully ionized, and consequently it is an extremely efficient biological catalyst [1]. It has been suggested that up to 100 selenoproteins may exist in mammalian systems [2], and up to 30 have been identified by (&Se labelling in vivo [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions the Se in selenocysteine is almost fully ionized, and consequently it is an extremely efficient biological catalyst [1]. It has been suggested that up to 100 selenoproteins may exist in mammalian systems [2], and up to 30 have been identified by (&Se labelling in vivo [3].…”
Section: Introductionmentioning
confidence: 99%
“…These include four glutathione peroxidase enzymes, which represent a major class of functionally important selenoproteins. The Se peroxidases are genetically, structurally and kinetically different, and yet have both common and individual functions [1]. Classical glutathione peroxidase (GPi1), so called because it was the first to be discovered, is present in the cell cytosol, where it functions as an antioxidant by directly reducing H # O # and lipid hydroperoxides [5].…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes provide mechanisms by which intracellular biological structures are protected against potentially damaging effects of peroxide free radical-mediated attacks. 1 There is also increasing evidence that Se plays an important protective role both in the human immune system and in the prevention and suppression of a number of specific disorders such as carcinomas, cardiovascular diseases, cystic fibrosis and low fertility. [2][3][4] Despite its dietary significance, Se is an element for which the concentration range from trace element requirement to toxicity is relatively narrow.…”
Section: Introductionmentioning
confidence: 99%
“…These include four glutathione peroxidase enzymes (classical GPx1, gastrointestinal GPx2, plasma GPx3, phospholipid hydroperoxide GPx4) which represent a major class of functionally important selenoproteins. The Se peroxidases are genetically, structurally and kinetically different yet have both common and individual functions 3 .…”
Section: Selenoproteinsmentioning
confidence: 99%